Colouration as a signal of health status. The effects of diet, parasites and androgens on the expression of colour in the European Serin (Serinus serinus). - Trigo, Sandra Cristina de Sousa (2015)
Tese de Doutoramento em Biologia, Especialidade de Ecologia, apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra